An Advanced Materials Beamline for Energy Research (AMBER). Issue 2 (4th March 2017) - Glans, Per-Anders; Liu, Yi-Sheng; Crumlin, Ethan; Yang, Wanli; Warwick, Tony; Hussain, Zahid; Guo, Jinghua
Abstract : Detailed mapping of the electronic structure is a crucial part of explaining the behavior of materials. It is the electronic structure that determines the conductivity and thermal properties. It is the electronic structure that determines chemical properties. Knowledge about the electronic structure can help in determining the atomic structure of molecules.